Effectiveness of PPE For Prevention of Occupational Ocular Injury - Iwan Susilo Joko; Dewi S Soemarko; Nuri Purwito Adi (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background: One of the risk factors for Chronic Lymphocytic Leukemia (CLL) is chemical exposure at work. The aim is to determine the relationship between patient who work as a farmer and vegetable seller with the incidence of CLL.Case presentation: A-69-year-old man who has been working as a vegetable seller since 15 years and a chili farmer since 4 years ago. The patient was diagnosed with CLL. In his work as a vegetable seller and chili farmer, the patient gets five hazards ranging from physical, chemical, biological, ergonomic and psychosocial hazards so it is necessary to analyze whether there is a relationship between the patient’s work and the current CLL disease.Discussion: There are seven steps needed in the enforcement of occupational diseases. In addition, additional examinations are needed to determine the biomarkers of pesticides that can cause disease. This requires control for farmers and vegetable sellers who may be exposed to pesticides found in vegetables and chilies. Conclusion: Vegetable seller and farmer have potential hazards, especially chemicals contained in pesticides which have a risk relationship with the incidence of CLL. However, to cause CLL, sufficient doses are required which are influenced by occupation, intensity of use and the type of specific chemical without the need for a long duration of exposure.